A modified method for constructing experimental rat periodontitis model - Zhang, Xuyang; Xu, Minglu; Xue, Qin; He, Yao (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Periodontitis is a prevalent disease caused teeth lost. The present rat models inducing periodontitis with thread ligature and metal steel ligature have some disadvantages. Methods: We modified the existing rat ligature periodontitis model by fixing the thread ligature on the metal steel ligature passed through the gap between the first and second molars of rats with detailed modeling steps and illustrations. We research the pathological process of the periodontitis induced by the modified model, and briefly compared the modified model with the thread ligature model and the metal steel ligature model. Result: Our experimental results showed that there was an aggravation in inflammatory infiltration and alveolar bone resorption in modeling area within 14 days of initial induction. After that, the inflammatory infiltration was reduced. And no significant increase in alveolar bone destruction appeared. The modified model was more reliable compared to the thread ligature model, and had greater ability of bacterial aggregation compared to the metal steel ligature model. Conclusion: The modified method covered pathological process of the periodontitis, and showed sufficient efficiency and reliability in inducing rat periodontitis.